Penigkatan Keterampilan Menulis Puisi melalui Prinsip-prinsip Sugestologi Siswa Kelas VII.1 SMP N 4 VII Koto Sungai Sarik Kabupaten Padang Pariaman - Sufia Retti; Atmazaki .; Novia Juita (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: This research aimed: (1) to describe the process of student’s improvement in writing a poem Through Sugestology Principles at class VII. I SMP N 4 VII Koto Sungai Sarik of Padang Pariaman Regency, (2) to describe some influential factor to student’s improvement in writing a poem Through Sugestology Principles at class VII. I SMP N 4 VII Koto Sungai Sarik of Padang Pariaman Regency. The type of this research was class room action. It was conducted in two cycles with four meetings. Each cycle used four stages, were planning, action, observation or evaluation and reflection. The data of this research was obtained in the form of qualitative and quantitative data. Qualitative data was collected from the observation and field notes. Other was obtained from students’ performance test and questionnaire of student’s response toward the teaching-learning process. Based on the research result showed that the implementation of suggestology principles in teaching writing a poem in fact can improve their skill in writing a poem. It can be seen from their result performance of average in a class in pre cycles, the average skill of writing in a class was 63.6%, after take an action, have happened the increase of their writing skill average was 72.6%, in the second cycles, their writing skill increased become 82.0%. some influential factor of student’s skill improvement in writing a poem were teacher’s actions or treatment in teaching learning process of writing a poem, an appropriately a teaching model used in teaching writing a poem, and comfortable condition was created by teacher. Kata kunci: keterampilan menulis, puisi, prinsip-prinsip sugestologi